Comparative analysis of corneal measurements obtained from a Scheimpflug camera and an integrated Placido‐optical coherence tomography device in normal and keratoconic eyes. (14th December 2014) - Viswanathan, Deepa; Kumar, Nikhil L.; Males, John J.; Graham, Stuart L.
Abstract Purpose To assess the agreement between a Scheimpflug camera (Pentacam) and a combined Placido‐optical coherence tomography device (Visante OMNI) in measuring corneal curvature, thickness and elevation values in normal and keratoconic eyes. Methods Corneal measurements of 110 normal eyes (one eye per subject) and 70 keratoconic eyes were obtained from both devices and compared. Agreement was determined using the Bland–Altman analysis 95% limits of agreement (LoA). Results The Pentacam measured significantly greater keratometry readings in the flattest (K1) and steepest meridians (K2) in normal and keratoconic eyes. The 95% LoA in normal eyes were −0.32 to 0.59 dioptres (D) (K1) and −0.41 to 0.74 D (K2). In keratoconic eyes, the 95% LoA were −1.35 to 1.92 D (K1) and −1.38 to 1.99 D (K2). The Pentacam recorded significantly higher central corneal thickness (CCT) values in both groups of eyes. The 95% LoA were −4.31 to 39.89 microns (μ) and −12.92 to 41.35 μ in normal and keratoconic eyes, respectively. Pentacam anterior and posterior corneal elevations were significantly greater in both groups of eyes. The devices demonstrated excellent repeatability and reproducibility for corneal curvature and thickness but not elevation measurements. Conclusions The Pentacam measured significantly greater corneal curvature, thickness and elevation values compared to the Visante OMNI in normal and keratoconic eyes. The devices agree moderately for anterior corneal elevations in normal eyes and do not appear to be interchangeable for corneal measurements in clinical practice.